2018
DOI: 10.1111/jvh.13003
|View full text |Cite
|
Sign up to set email alerts
|

Early emergence of opportunistic infections after starting direct‐acting antiviral drugs in HIV/HCV‐coinfected patients

Abstract: Varicella-zoster virus and hepatitis B virus reactivations have been reported after starting interferon-free direct-acting antiviral agent (DAA) combinations. HIV/HCV-coinfected patients could be a high-risk group for the reactivation of latent infections. Because of these, we report the occurrence of severe infections after starting DAA regimens in HIV/HCV-coinfected patients. Individuals included in the HEPAVIR-DAA (NCT02057003) cohort were selected if they had received all-oral DAA combinations. A retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Furthermore, there are reports of HBV and varicella-zoster reactivations following the start of DAA therapy [ 33 , 34 ]. There is also a description of increased incidence of opportunistic infections in HIV/HCV coinfected patients appearing around 23 weeks after the beginning of DAA therapy [ 35 ]. We cannot exclude that those observations may be related to the persistence of an increased number of circulating Treg cells after DAA therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there are reports of HBV and varicella-zoster reactivations following the start of DAA therapy [ 33 , 34 ]. There is also a description of increased incidence of opportunistic infections in HIV/HCV coinfected patients appearing around 23 weeks after the beginning of DAA therapy [ 35 ]. We cannot exclude that those observations may be related to the persistence of an increased number of circulating Treg cells after DAA therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, studies examining DAA-mediated cure of HCV, mostly in monoinfected subjects, suggest only partial reconstitution of immune functions and persistence of immune suppressive cells like Tregs and MDSC. This immune suppressive environment may contribute to reduced immune response to vaccinations, limited immune surveillance against cancer, and increased reactivation of latent or occult infections of herpesviruses and hepatitis B virus, respectively ( 240 , 241 ). Finally, this incomplete reconstitution of HCV-specific CD4 + and CD8 + T cells may increase the risk of HCV persistence upon re-exposure and reinfection in high-risk populations like PWID and MSM.…”
Section: Effect Of Daa-mediated Cure Of Hcv In Coinfected Subjectsmentioning
confidence: 99%
“…In summary, studies that describe DAA-mediated clearance of HCV, suggested only limited recovery of the immune system and an immune suppressive environment with persistence of cells like Tregs and MDSC. These immune suppressive conditions might decrease immune response to vaccinations, reduce immune surveillance against cancer, and increase re-activation of latent infections of herpesviruses and hepatitis B virus, respectively (Macias et al, 2019a;Fabbri et al, 2017). Finally, an incomplete reconstitution of HCV-specific CD4+ and CD8+ T cells might increase the risk of HCV persistence upon reexposure and re-infection in high-risk populations like HCV/HIV co-infected patients.…”
Section: Introductionmentioning
confidence: 99%